(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To perform morphometric analysis of retinal structural components in Wistar rats in experimental diabetes mellitus (DM) in an attempt to digitize possible retinal neurodegenerative changes. Material and Methods: Eight histological globe preparations from Wistar rats were retrospectively reviewed. Of these, five were from Wistar rats with experimental DM, and three, from healthy controls. Total retinal thickness was measured and thicknesses of the following retinal layers were measured: the photoreceptor layer (PRL), outer nuclear layer (ONL), outer retinal layer (ORL), inner nuclear layer (INL), ganglion cell layer (GCL), and nerve fiber layer (NFL). The numbers of neural-cell rows in both nuclear layers were calculated visually. Statistica 5.5 software was used for the analysis of measurement data. Results: The mean total thickness of the retina was 252.9 ± 8.77 µm for healthy controls and 262.1 ± 8.51 µm for diabetic animals. In controls and diabetic animals, the mean thicknesses for particular retinal layers were as follows: PRL, 75.5 ± 4.14 µm and 74.0 ± 3.85 µm, respectively; ONL, 61.8 ± 3.04 µm and 66.1 ± 4.12 µm, respectively; ORL, 11.6 ± 0.72 µm and 12.4 ± 0.64 µm, respectively; INL, 33.1 ± 1.74 µm and 33.6 ± 1.75 µm, respectively; IRL, 47.2 ± 2.77 µm and 47.9 ± 2.39 µm, respectively; and GCL plus NFL, 23.7 ± 1.44 µm and 28.1 ± 2.57 µm, respectively. In addition, the numbers of neural-cell rows in the ONL were 11.3 ± 0.50, and 11.7 ± 0.59, respectively, and in the INL, 4.6 ± 0.26, µm and 4.7 ± 0.17, respectively. There was no statistically significant difference in thicknesses of retinal layers or numbers of neural-cell rows in the INL and ONL of the retina between normal and diabetic rats. Conclusion: For Wistar rats with diabetes duration of 3 months, microscopic images of the retina and calculations of thicknesses of individual retinal layers and numbers of neural-cell rows in retinal nuclear layers provided no indication of neurodegenerative changes at this time point.